Marine Natural Products from Flora and Fauna of the Western Australian Coast: Taxonomy, Isolation and Biological Activity - Samuele Sala; Scott K. Micke; Gavin R. Flematti (Molecules, 2023)
Marine natural products occurring along the Western Australian coastline are the focus of this review. Western Australia covers one-third of the Australian coast, from tropical waters in the far north of the state to cooler temperate and Antarctic waters in the south. Over 40 years of research has resulted in the identification of a number of different types of secondary metabolites including terpenoids, alkaloids, polyketides, fatty acid derivatives, peptides and arsenic-containing natural products. Many of these compounds have been reported to display a variety of bioactivities. A description of the compound classes and their associated bioactivities from marine organisms found along the Western Australian coastline is presented.